The effect of tailwater depth on the local scour downstream of stepped-chutes - Emiroglu, M. Emin; Tuna, M. Cihat (Korean Society of Civil Engineers-Ksce, 2011)
This paper reports on an experimental study of the effect of tailwater depth on local scour downstream of stepped-chutes. Different tailwater conditions were tested to study the form of the scour for two gradations of non-cohesive bed material, various flow rates, chute angles, sill heights and step heights. Measurements were taken to obtain the scour hole profile in the equilibrium state of scour, the value of the maximum depth of scour, the location of the maximum scour depth, and the length of the scour hole. The present results indicate that maximum depth and area of scour are highly dependent on tailwater depth. Moreover, the maximum scour depth increases with increases in the discharge and the tailwater depth. It was also found that step geometry, stepped chute angle and the sill types of the stilling basin are very important parameters for scour hole and geometry. A comparison was made between the scour characteristics produced by different tailwater depths. Empirical correlations predicting maximum scour depth were developed. Hence, accurate equations for the maximum scour depth are introduced.
Keywords: local scour; stepped-chute; stepped spillway; stepped-channel chute; tailwater; hydraulic structures